A concepção de professor presente em textos de apresentação de livros didáticos de português dos anos 1990, 2000, 2010 - Vargas, Adriana Trindade (2014)
The present study aims to investigate the evaluative positions of the authors on the conception of teacher in presentation texts and in guidelines to the teacher in textual production activities in three Portuguese textbooks of distinct collections from the years of 1990, 2000, 2010. This research is grounded in Bakhtin's theoretical perspective for analysis and interpretation of materials. The utterances were described, analyzed and interpreted taking into account the historical and social time in which the sayings of the authors were constructed and the relations between these utterances were established the so-called dialogical relations, which are relations of sense. From the analysis and dialogical relationships established, we identified a conception of teacher common to the three presentation texts, a subject teacher as limited connoisseur, expression with different nuances of meaning arising from singularities present in the sayings of each textbook author. We also noted that the conception of teacher in these presentation texts is confirmed in the guidelines to the teacher in textual production activities from the textbooks. We believe it is not coincidental that unique way of conceiving the teacher, but it is a new trend in how to understand the figure of the teacher demanded by the own way of how to understand Portuguese language teaching as a mother tongue in an education system at a particular time.